2019
DOI: 10.1186/s41065-019-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of Capsicum annuum as revealed by start codon targeted and directed amplified minisatellite DNA markers

Abstract: Background Identification of high resolving DNA-based markers is of paramount importance to unlock the potential of genetic diversity and selection of unique accessions of Capsicum annuum L., within Cross River and Ebonyi States of Nigeria, for breeding and conservation. Therefore, we comparatively explored the effectiveness of start codon targeted (SCoT) and directed amplified minisatellite DNA (DAMD) markers for diversity analysis of the accessions. Fifteen accessions were collected for DNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Molecular markers techniques and gene chip arrays have been applied in the last decades for pepper germplasm characterization [3][4][5][6][7][8][9][10] with the goal to provide complementary descriptors to conventional morphological variation. However, triggered by advancements in sequencing technologies, the genome sequence of several crop Genome assembly and reconstruction.…”
mentioning
confidence: 99%
“…Molecular markers techniques and gene chip arrays have been applied in the last decades for pepper germplasm characterization [3][4][5][6][7][8][9][10] with the goal to provide complementary descriptors to conventional morphological variation. However, triggered by advancements in sequencing technologies, the genome sequence of several crop Genome assembly and reconstruction.…”
mentioning
confidence: 99%
“…The average value of population genetic diversity is 0.21, which is higher than the previous analysis in Polygonatum (H = 0.1943, H = 0.1279) (Feng et al 2020), indicating that SCoT markers are more superior than EST-SSR markers and SRAP markers. However, in previous reports that also used SCoT markers, H values were found to be lower than in Capsicum annuum (H = 0.5936) and Miscanthus lutarioriparius (H = 0.32), which may be due to different germplasm or the number of individuals in the population (Igwe et al 2019;Yang et al 2019). The average value of genetic diversity in SCoT marker is 0.3286, which also indicates that SCoT marker is highly polymorphic.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the SCoT markers detected 64 polymorphic loci (NPL), the percentage polymorphic loci (PPL) ranged from 80.00-95.73%, and estimation of gene flow was 3.84. This study showed that SCoT markers may be more useful and 14 informative in measuring genetic diversity and differentiation of the accessions of the genus Capsicum (Igwe et al, 2019).…”
Section: Start Codon Targeted (Scot) Markermentioning
confidence: 84%